Migration as opportunity for rural regions - Wibke Strahl; Ingrid Machold; Thomas Dax (European Regional Science Association (ERSA), 2012)
In spite of an unbroken interest of migrants for metropolitan areas and cities, the immigration of foreign people into rural, and as well peripheral, regions of Austria increasingly receives attention over recent years. Actually, 21% of the population of foreign origin live in municipalities with less than 5,000 inhabitants. In more and more peripheral regions population losses caused by a low birth rate and a negative internal migration can be significantly reduced by a positive external (i.e. international) migration balance. These demographic changes lead also to an increase in the diversity of society of rural regions. Many analysts underpin the additional potential provided through a multi-cultural society resulting in new ideas and innovative activities for regional policy, in addition to the more popular concerns for adaptation and integration challenges. This paper draws from a national project on international migration processes and their impact on rural regions of Austria, providing an analysis of statistical data of internal and external migration flows, changes in the demographic structure, and differentiation of migrants according to their countries of origin for the period 2002-2010. The analysis is carried out at the regional level of NUTS 3 and uses the up-dated EU-Commission's classification based on the OECD typology (Dijkstra and Poelman 2008). Furthermore, the paper will offer initial insights into empirical data about the motivation of immigrants to settle in rural regions and their functions within local communities. Thus, the paper focuses on the assessment of development opportunities for rural regions which are characterized by shrinking processes and the related challenges in terms of maintaining services of general interests, which could benefit from migration processes. The regional manifestations of these migration processes are systematically analysed so as to filter out so-called migration "hot spots" in Austrian rural regions. On this basis two case study regions were selected for empirical investigations about motives, challenges and socio-economic impacts of immigrants on remote rural areas. Information, gained primarily by face-to-face interviews and focus groups conversations both among migrants and the host society itself, and case studies from the current implementation of the key activity "diversity and space" of the new Austrian Spatial Development Concept (ÖREK 2011) will be presented.
Keywords: 330